The Centrality of The Qur'an in Establishing a Culture of Non-Violence from The Perspective of Badie Al-Zaman: Reading Reality and Looking for Solutions - Idris Qader Hamadameen; Farhad Ibrahim Akbar AL-SHwany (QALAAI ZANIST JOURNAL, 2024)
Competition and conflict over the ephemeral wreckage of the world, violent fighting over access to material benefits, control of power and the extension of influence in any way are horrific events that have plagued humanity around the globe, to the extent that the entire human entity is threatened by great dangers that diminish its existential and values, and lead it towards sexual or moral annihilation. A culture based on the indifference to material and moral benefits of what is forbidden and prohibited is the basis for the violence that is taking place in human societies today, resulting in the crystallization of aggressive concepts that souls and characters are almost accustomed to in their behaviour and communication. Due to seriousness of this miserable reality that has led us to choose a vital subject that sees us with radical solutions that will help humanity to correct its reality in order to return to the origin of its pure and rich nature, and to take peace, tolerance and justice as the basis for perfection and transcendence, and then enjoy happiness and bliss, all in accordance with a decreed approach based on Qur'anic origins and divine foundations. Hence, the subject of our research was led by a title closely related to what we mentioned earlier: (The Centrality of The Qur'an in Establishing a Culture of Non-Violence from The Perspective of Badie Al-Zaman - Reading Reality and Looking for Solutions). Badie Al-Zaman Saeed Al-Noursi's view of this subject stems from his suffering and observations of the painful events that ravaged humanity during the First and Second World Wars, as the world witnessed tragedies and woes at the time, the ruin has long gone on, feeling and conscience, so the situation became a trivial, and the reality is dead, so Al-Noursi tried with the Qur'anic sciences to find solutions to what happened, and this deteriorating reality is corrected by medicines inspired by the pharmacy of the Holy Quran.